Mediastinal peripheral T‐cell lymphoma diagnosed by repeated biopsies after an initial diagnosis of fibrosing mediastinitis. Issue 6 (18th September 2017) - Kakuta, Naoko; Sumitani, Mitsuhiro; Sugitani, Arata; Nakahama, Kenji; Miki, Yuzo; Syoji, Seichi
Abstract : We report a case of mediastinal peripheral T‐cell lymphoma not otherwise specified (PTCL‐NOS) diagnosed by repeated biopsies. A 44‐year‐old man was admitted to our hospital with a 2‐week history of facial swelling, neck distension, and dyspnoea on exertion. Computed tomography of the chest showed a mediastinal mass. Initial needle biopsy and video‐assisted thoracoscopic biopsy revealed the pathological diagnosis of fibrosing mediastinitis (FM). Glucocorticoid therapy (prednisolone) was temporarily effective in reducing tumour size. However, other laboratory features suggested that the diagnosis of FM might not be correct. After repeated biopsies, we established the diagnosis of mediastinal PTCL‐NOS. With this correct diagnosis, appropriate therapy for PTCL resulted in the improvement of the clinical manifestations. This report suggests that the presence of malignant lymphoma should be considered in cases of mediastinal tumours, and repeated biopsies may be occasionally needed for consistent diagnosis. Abstract : Initial needle biopsy and video‐assisted thoracoscopic biopsy revealed the pathological diagnosis of fibrosing mediastinitis for mediastinal mass. However, other laboratory features suggested that the diagnosis of fibrosing mediastinitis might not be correct. Finally, a fourth biopsy established the diagnosis of mediastinal PTCL‐NOS.